DOI: 10.4995/thesis/10251/16878
|View full text |Cite
|
Sign up to set email alerts
|

Methodology for the Numerical Characterization of a Radial Turbine under Steady and Pulsating Flow

Abstract: iii AbstractThe increasing use of turbochargers is leading to an outstanding research to understand the internal flow in turbomachines. In this frame, computational fluid dynamics (CFD) is one of the tools that can be applied to contribute to the analysis of the fluid-dynamic processes occurring in a turbine. The objective of this thesis is the development of a methodology for performing simulations of radial turbomachinery optimizing the available computational resources. This methodology is used for the char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…During the past two decades, two main turbulence models have been developed: k − model, which is based on the turbulence dissipation rate , and k − ω model, which is based on the specific dissipation rate ω. Fajardo [60] indicated that k − ω is more accurate than k − in computing the near-wall layers. However, k − converges faster and is robust with real gas applications [36].…”
Section: Turbulence Model Physical Domain Boundary Conditions and mentioning
confidence: 99%
“…During the past two decades, two main turbulence models have been developed: k − model, which is based on the turbulence dissipation rate , and k − ω model, which is based on the specific dissipation rate ω. Fajardo [60] indicated that k − ω is more accurate than k − in computing the near-wall layers. However, k − converges faster and is robust with real gas applications [36].…”
Section: Turbulence Model Physical Domain Boundary Conditions and mentioning
confidence: 99%
“…Thus, it is less effective to investigate this problem using only the MOC or only the CFD method. However, a hybrid approach making use of each technique is likely to be a more efficient approach [16][17][18][19][20]. Yang et al [16] applied this coupling method to study the dynamic characteristics of a pump response to transient events.…”
Section: Introductionmentioning
confidence: 99%
“…Mandair et al [18] compared the MOC method with a full CFD simulation for a very simplified case involving the water hammer caused by the rapid closure of a knife edge valve, and compared the results with a water hammer experiment. Some other researchers [19][20] applied this coupling approach to gas service. All of these studies indicate that the hybrid coupling approach can improve accuracy at the coupling interfaces for relatively 4 simple geometries.…”
Section: Introductionmentioning
confidence: 99%
“…Mandair et al [18] compared the MOC method with a full CFD simulation for a very simplified case involving the water hammer caused by the rapid closure of a knife edge valve, and compared the results with a water hammer experiment. Some other researchers [19][20] applied this coupling approach to gas service. All of these studies indicate that the hybrid coupling approach can improve accuracy at the coupling interfaces for relatively simple geometries.…”
Section: Introductionmentioning
confidence: 99%